2018
DOI: 10.3390/nano8100816
|View full text |Cite
|
Sign up to set email alerts
|

A Solvothermal Synthesis of TiO2 Nanoparticles in a Non-Polar Medium to Prepare Highly Stable Nanofluids with Improved Thermal Properties

Abstract: Nanofluids are systems with several interesting heat transfer applications, but it can be a challenge to obtain highly stable suspensions. One way to overcome this challenge is to create the appropriate conditions to disperse the nanomaterial in the fluid. However, when the heat transfer fluid used is a non-polar organic oil, there are complications due to the low polarity of this solvent. Therefore, this study introduces a method to synthesize TiO2 nanoparticles inside a non-polar fluid typically used in heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…The peaks were observed at 151, 403, 518 and 639 cm −1 for the powder treated at 100 °C and at 144, 397, 516 and 636 cm −1 for that at 400 °C, and are attributed [41] to the vibration symmetries E g , B 1g , A 1g /B 1g and E g , respectively. The active mode shift at 151 cm −1 observed in the sample treated at 100 °C in neutral medium could be related to low crystallinity and to the presence of oxygen vacancies in the TiO 2 structure, as reported in literature [42,43]. The samples treated at the highest temperature (T C = 800 °C) showed three optical phonon peaks of the rutile phase: a very low-intensity mode centred at 143 cm −1 and two highintensity modes at 446 and 609 cm −1 , related to the B 1g , E g and A 1g symmetries, respectively.…”
Section: Raman Characterizationsupporting
confidence: 74%
“…The peaks were observed at 151, 403, 518 and 639 cm −1 for the powder treated at 100 °C and at 144, 397, 516 and 636 cm −1 for that at 400 °C, and are attributed [41] to the vibration symmetries E g , B 1g , A 1g /B 1g and E g , respectively. The active mode shift at 151 cm −1 observed in the sample treated at 100 °C in neutral medium could be related to low crystallinity and to the presence of oxygen vacancies in the TiO 2 structure, as reported in literature [42,43]. The samples treated at the highest temperature (T C = 800 °C) showed three optical phonon peaks of the rutile phase: a very low-intensity mode centred at 143 cm −1 and two highintensity modes at 446 and 609 cm −1 , related to the B 1g , E g and A 1g symmetries, respectively.…”
Section: Raman Characterizationsupporting
confidence: 74%
“…A broad band can be observed between 1000 and 400 cm −1 , which is originated from the bending vibration of Ti-O-Ti. [19][20][21] Furthermore, it was found that after treating TiO 2 (A) nanofibers with NaOH, the feature peak intensity of the -OH stretching vibration at 3444 cm −1 was obviously increased as compared to that of the normal TiO 2 (A) nanofibers. 21 This result reveals that during the activation pretreatment process, the TiO 2 surface could be slightly etched with NaOH to allow the exposure of lattice O and Ti on the TiO 2 surface, thereby increasing the amount of hydroxyl groups adsorbed on the TiO 2 surface.…”
Section: Papermentioning
confidence: 99%
“…[19][20][21] Furthermore, it was found that after treating TiO 2 (A) nanofibers with NaOH, the feature peak intensity of the -OH stretching vibration at 3444 cm −1 was obviously increased as compared to that of the normal TiO 2 (A) nanofibers. 21 This result reveals that during the activation pretreatment process, the TiO 2 surface could be slightly etched with NaOH to allow the exposure of lattice O and Ti on the TiO 2 surface, thereby increasing the amount of hydroxyl groups adsorbed on the TiO 2 surface. The emergence of -OH connected with lattice Ti would offer a chemical bridge for enabling UiO-66-NH 2 to load on the TiO 2 (A) nanofibers.…”
Section: Papermentioning
confidence: 99%
“…Nanofluids (colloidal suspensions of nanomaterials) [1] have been widely studied for more than two decades by researchers motivated by their enhanced thermophysical properties over conventional heat transfer fluids [2], and potential applications, particularly, in solar energy conversion processes [3][4][5][6][7][8][9][10][11][12][13]. Concentrating solar power (CSP) is a renewable technology that can largely benefit from nanofluids, as heat transfer fluids (HTF), to improve the efficiency of solar-to-thermal-to-electric energy conversion.…”
Section: Introductionmentioning
confidence: 99%